Consumption, Dividends, and the Cross Section of Equity Returns - BANSAL, RAVI; DITTMAR, ROBERT F.; LUNDBLAD, CHRISTIAN T. (Journal of Finance, 2005)
ABSTRACT We show that aggregate consumption risks embodied in cash flows can account for the puzzling differences in risk premia across book‐to‐market, momentum, and size‐sorted portfolios. The dynamics of aggregate consumption and cash flow growth rates, modeled as a vector autoregression, are used to measure the consumption beta of discounted cash flows. Differences in these cash flow betas account for more than 60% of the cross‐sectional variation in risk premia. The market price for risk in cash flows is highly significant. We argue that cash flow risk is important for interpreting differences in risk compensation across assets.